PERAN KUNCI DALAM DINAMIKA PENDIDIKAN ISLAM (SEJARAH DAN PERKEMBANGAN SUMATERA THAWALIB) - Hidayah, Nurul; Devandri, Fikriar; Arief (CV. ADIBA ASIHA AMIRA, 2024)
This research aims to examine the history and development of Sumatra Thawalib as one of the oldest Islamic educational institutions in Indonesia, as well as its role in the transformation of modern Islamic education in the archipelago. The research method used is a historical method, with a descriptive-analytical approach based on literature studies and relevant archival documentation. The research results show that Sumatra Thawalib played an important role in the change in the Islamic education system from traditional to modern at the beginning of the 20th century. This institution plays a pioneering role in adopting a more systematic curriculum, introducing general sciences, and spreading Islamic reform ideas in Indonesia. The discussion in this research reveals that the development of Sumatra Thawalib not only had an impact on the transformation of education in West Sumatra, but also made a significant contribution to the intellectual movement and socio-religious reform in Indonesia more broadly. In conclusion, Sumatra Thawalib has succeeded in becoming a symbol of Islamic educational reform that combines Islamic values with advances in modern science, as well as becoming a foundation for the development of other Islamic educational institutions in Indonesia.